Restructuring platform merger review - Sung Ick Cho (Korea Development Institute (KDI), 2023)
Platform mergers differ significantly from traditional mergers. In platform mergers, foreclosure issues, which are crucial in traditional vertical mergers, carry less significance but may still arise indirectly. Platforms, moreover, can favor their own businesses potentially disadvantaging competitors, and leverage their market power to new businesses. Lastly, entry barriers could increase as a result of platforms' multi-service provisions. Nevertheless, platforms can enhance consumer welfare, especially through product (service) bundling. Thus, we need to overhaul the merger review system to incorporate the aforementioned characteristics of platform mergers.
Keywords: 330